Ectemnaspis or Psilopelmia? there is the dilemma - MIRANDA-ESQUIVEL, DANIEL RAFAEL; MUÑOZ DE HOYOS, PAULINA (Revista Colombiana de Entomología, 1995)
The difficulty to define the species limits of Ectemnaspis or Psilopelmia arises from two opposite points of view from Coscarón (1984, 1987 y 1990) and Crosskey (1987). To define the monophyly and the sister group of Ectemnaspis-Psik,)Pelmia the data from Coscarón (1987) and Coscarón et al. (In press) were bootstrapped. To know the subgeneric position two different information sources were used: morphology and chromosome banding. In the cladistic examination from morphological data, fourteen taxa were selected, which cover all the possibilities to be estimated as Psilopelmia or Ectemnaspis from both authors or have problems in the subgeneric position. Forty-eight characters from larva, pupa, adult female and male were chosen. As a sister group, the species S. oviedoi- S. rivasi, S. pertinax and S. subpasllium were used. In the chromosome analysis, seven species and 12 characters were used: principal and secondary markers from chromosome I -III. The species represent the bicoloratum, romanai and dinellii groups. As the sister group, it was selected the Simulium subgenus map. With the morphological and chromosomal data, separated and as a set, a parsimony cladistic analysis was conducted. The results show at least five independent units: romanai, bicoloratum, dinéllii, perflavum, and Psilopelmia. To be consistent with the actual nomanclature the sub-groups must get the subgeneric status.